Risk Analysis and Crisis Management: A Proactive Approach to Overcoming Business Uncertainty - Edie Riesnanda Wahyu (PT. Publikasiku Academic Solution, 2023)
A crisis is a rumor, event and information that has an impact on the good name, image and trustworthiness of a company. In fact, the crisis that occurred did not only impact large companies, but small businesses were one of the groups most affected by the Covid-19 pandemic crisis. Therefore, all parties, both individuals and companies, must be prepared to face a crisis. Crisis management is defined as a set of factors created as a tool to eradicate a crisis and reduce the potential damage resulting from the crisis. This research aims to find out how a business is able to survive, what strategies are prepared to overcome uncertainty in business. This research uses a qualitative descriptive method using a case study method which seeks to understand the whole and in depth of a case, data collection methods using literature studies sourced from journals or other online media. The results of this research are that UMKM business actors survive by using several strategies such as utilizing digital technology, improving product and service quality, pricing and customer relationship marketing. Large business players use strategy by forming a management team, identifying, analyzing, developing planning, communication and evaluation methods.